Free vibration of a thin circular cylindrical shell on three-parameter elastic foundation, using wave propagation approach - Paliwal, D. N.; Katiyar, Lawkesh Kr. (Journal of Structural Engineering, 2024)
A solution for free vibration of thin circular cylindrical shell resting on a three-parameter Levinson-Bharatha model of elastic foundation, using wave propagation approach is proposed. Results are reduced to two-parameter Pasternak foundation and are matched with the results obtained by Paliwal, Pandey and Shukla. Eigen frequencies are obtained for simply supported, clamped-clamped and clamped-shear diaphragm boundary conditions. Analysis based on Flugge classical thin shell theory is performed. We see that wave propagation is an efficient method for calculating the frequency of circular cylindrical shell resting on elastic foundation.